MATERNAL AND FOETAL OUTCOME IN GESTATIONAL DIABETES - Qadir, Saima Yasmin; Yasmin, Tayyaba; Fatima, Iffat (Journal of Ayub Medical College Abbottabad, 2012)
Background: Gestational diabetes is impaired carbohydrate metabolism first diagnosed in pregnancy. Knowledge of diabetes dates back to centuries before Christ. Objective was to describe maternal complications during antenatal period and Maternal and neonatal outcome in gestational diabetes mellitus. Methods: This Descriptive observational study was conducted at Department of Obstetrics and Gynaecology, Alhada Military Hospital, Taif, KSA. It was done during January-December 2009 to measure maternal and neonatal outcome. Hundred pregnant women diagnosed through glucose tolerance test as diabetic were enrolled as study subjects. All the subjects were enrolled and followed regularly at Obstetric and Gynaecology out-patient Department of Alhada Military Hospital, Taif. Blood glucose level was controlled either by diet or by diet and insulin. Study subjects were hospitalised for adjustment of dose of insulin and for management of complications. Foetal well being was assessed by kick count, cardiotocography and ultrasound. Time and mode of delivery was decided at 36 week of gestation. Intra-partum maternal blood glucose level was monitored and foetal monitoring was done by cardiotocography. Results: Total numbers of women delivered were 2,858. Hundred cases of diabetes mellitus during pregnancy were studied. Eighty-eight patients were above 25 years of age, multiparous ladies with gestational diabetes in 76% of cases. Insulin was required in 64% of patients. Polyhydramnios was most common maternal complication. Two out of 100 had spontaneous miscarriage; 14 underwent preterm delivery while 84 reached term with two intrauterine death. Caesarean section was carried out in 58 patients. Total number of babies delivered alive were 92. There were 4 neonatal deaths. Hyperbilirubinemia was the most common neonatal complication. Conclusion: It was concluded that early detection, constant supervision, strict glycaemic control, delivery with intensive intrapartum monitoring and facilities of expert neonatologist can result in good maternal and foetal outcome, without much morbidity. Keywords: Pregnancy, Gestational diabetes mellitus, Maternal outcome, Neonatal outcome